OUTCOMES OF MAINTENANCE MONOTHERAPY WITH GEMCITABINE IN METASTATIC NASOPHARYNGEAL CARCINOMA AT NGHE AN ONCOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To assess survival outcomes and safety of single-agent Gemcitabine maintenance in patients with metastatic nasopharyngeal carcinoma who achieved disease control after Platinum-based chemotherapy.Subjects and methods: This longitudinal descriptive study combined retrospective data collection with prospective follow-up and included 46 patients treated at Nghe An Oncology Hospital between January 2018 and June 2026. Patients with complete response, partial response, or stable disease after Platinum-based chemotherapy received Gemcitabine 1250 mg/m² on days 1 and 8 of a 21-day cycle until disease progression or unacceptable toxicity. Tumor response and adverse events were evaluated using RECIST 1.1 and CTCAE 5.0, respectively; PFS and OS was estimated by the Kaplan-Meier method.Results: The mean age of the patients was 52.80 ± 13.76 years; 78.3% were male and 93.5% had undifferentiated histology. Recurrent metastatic disease accounted for 69.6% of cases, while 87% had multiple metastatic lesions. The objective response rate after induction chemotherapy was 78.3%. The median number of maintenance cycles was 3.5 (range, 3-20). Median PFS was 17.45 months, with 6-, 12-, and 24-month PFS rates of 89.1%, 73.9%, and 42.4%, respectively. Median OS was not reached; the corresponding OS rates were 97.8%, 93.5%, and 82%. Grade 3-4 toxicity occurred in 41.3% of patients, mainly neutropenia (37%); no grade 3-4 non-hematologic toxicity was recorded.Conclusion: Single-agent Gemcitabine maintenance was associated with favorable observed survival outcomes and manageable toxicity in patients with recurrent or metastatic nasopharyngeal carcinoma who had achieved disease control after Platinum-based chemotherapy.
Keywords: Nasopharyngeal carcinoma, metastatic disease, maintenance therapy, Gemcitabine.